Śrīkrṣṇarāmāyaṇa vacanamu : Śrīpāda Krṣṇamūrtiśāstrigāru racincina "Śrīkrṣṇa Rāmāyaṇamu" naku anuvādamu - Viśālākṣamma, Kallūri (SAMP early 20th-century Indian books project ;, 1948)
Prose version of the Śrīkrṣṇa Rāmāyaṇamu, Telugu poetical work on Rāma, Hindu deity, by Śrīpāda Krṣṇamūrtiśāstri, 1866-1960, Telugu litterateur.